Fomepizole versus ethanol in the treatment of acute methanol poisoning: Comparison of clinical effectiveness in a mass poisoning outbreak - Zakharov, Sergey; Pelclova, Daniela; Navratil, Tomas; Belacek, Jaromir; Komarc, Martin; Eddleston, Michael; Hovda, Knut Erik (Clinical toxicology (Philadelphia, Pa.), 2015)
CONTEXT: Mass or cluster methanol poisonings are frequently reported from around the world. The comparative effectiveness of ethanol and fomepizole as antidotes for methanol poisoning is unknown due to the difficulty of performing a randomized controlled trial. OBJECTIVE: During an outbreak of mass poisonings in the Czech Republic in 2012-2014, we compared the effects of antidotes on the frequency of health sequelae and mortality. METHODS: The study was designed as a cross-sectional case series and quasi-case-control study. Patients with a diagnosis of methanol poisoning on admission to hospitals were identified for the study. Diagnosis was established when (i) a history of recent ingestion of illicit spirits was available and serum methanol was higher than 6.2 mmol/L (20 mg/dL), or (ii) there was a history/clinical suspicion of methanol poisoning, and serum methanol was above the limit of detection with at least two of the following: pH < 7.3, serum bicarbonate < 20 mmol/L, and anion gap or AG ≥ 20 mmol/L. Fomepizole was given as a bolus dose of 15 mg/kg i.v. diluted in isotonic saline, followed by 10 mg/kg every 12 h (every 4 h during hemodialysis); ethanol was administered both intravenously as a 10% solution in 5% glucose, and per os in boluses of 20% solution. Multivariate regression was applied to determine the effect of antidote on outcome. Additionally, for a retrospective quasi-case-control study, a control group of patients treated with ethanol, matched carefully on severity of poisoning and other key parameters, was selected. RESULTS: Data were obtained from 100 hospitalized patients with confirmed poisoning: 25 patients treated with fomepizole were compared with 68 patients receiving ethanol (seven patients did not receive any antidote). More severely acidotic (p < 0.001) and late-presenting (>12 h; p = 0.028) patients received fomepizole more often than ethanol, as reflected in the higher number of fomepizole-treated patients being intubated (p = 0.009). No association was found between the type of antidote and the survival in either the case series (p = 0.205) or the quasi-control groups (p = 0.705) in which patients were very closely matched to minimize confounding by allocation. In the multivariate analysis, positive serum ethanol (odds ratio [OR], 10.8; 95% confidence interval [CI], 2.9-39.9) and arterial blood pH (OR, 3.7; 95% CI, 1.3-10.5) on admission were the only independent variables for the survival. The median intensive care unit length of stay was 6 (range, 2-22) days in the fomepizole group and 4 (range, 1-33) days in the ethanol group (p = 0.131). There were no differences in the use of elimination techniques between the two groups (neither in the full material (n = 100), nor the case-control groups (n = 50)). CONCLUSIONS: This study on antidotes for methanol poisoning did not show any evidence of different clinical effectiveness. Although ethanol is generally associated with a higher incidence of complications, this study suggests that both antidotes are similarly effective and that ethanol should not be avoided on grounds of effectiveness.
Keywords: rozvrh dávkování léků; dospělí; jednotky intenzivní péče; methanol; Antidote administration; logistické modely; Chi-Square Distribution; hodnocení rizik; Female; antidota; Fomepizole; Administration, Intravenous; multivariační analýza; ethanol; Adult; výsledek terapie; ženské pohlaví; mladý dospělý; průřezové studie; intravenózní podání; Linear Models; Logistic Models; Multivariate Analysis; Adolescent; Pyrazoles; časové faktory; Time Factors; lidé; pyrazoly; Methanol; Drug Administration Schedule; Antidotes; Treatment Outcome; Treatment outcome; Intensive Care Units; lineární modely; délka pobytu; otrava; Ethanol; hospitalizace; Risk Assessment; Length of Stay; Poisoning; Risk Factors; retrospektivní studie; Cross-Sectional Studies; Disease Outbreaks; Male; Aged; Czech Republic; Clinical effectiveness; Hospital treatment; Hospitalization; Young Adult; Sequelae of poisoning; rizikové faktory; rozdělení chí kvadrát; Česká republika; lidé středního věku; epidemický výskyt choroby; senioři; mužské pohlaví; fomepizol; Retrospective Studies; Middle Aged; mladiství; Humans